2006
DOI: 10.1111/j.1756-2171.2006.tb00031.x
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of extended liability

Abstract: Abstract:We characterize the optimal regulation of a firm which undertakes an environmentally risky activity. This firm (the agent) is protected by limited liability and bound by contract to a stakeholder (the principal). A key feature is the non-observability of the level of safety care exerted by the agent. This level of care depends both on the degree of incompleteness of the regulatory contract (i.e., whether private transactions can be controlled or not) and on the allocation of bargaining power between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 22 publications
2
36
0
2
Order By: Relevance
“…18 If the high effort cannot be supported, then the junior debtholders would demand an interest rate above 11%, further diluting the entrepreneur's incentives.…”
Section: Examplementioning
confidence: 99%
“…18 If the high effort cannot be supported, then the junior debtholders would demand an interest rate above 11%, further diluting the entrepreneur's incentives.…”
Section: Examplementioning
confidence: 99%
“…De par ses forte références à CERCLA, l'analyse économique contemporaine d'auteurs tels que Hiriart et Martimort (2006), Dionne et Spaeter (2003), Boyer et Porrini (2006 7 par exemple, continue d'être influencée par les travaux réalisées ante les amendements de 1996 par Boyer et Laffont (1995), Boyer et Laffont (1997), Pitchford(1995) 8 . Il en découle le hiatus évoqué entre la pratique juridique qui repousse, voire institutionnalise, l'irresponsabilité des prêteurs et la théorie économique qui, au contraire, considère acquise cette responsabilité.…”
unclassified
“…Since insolvency and limited liability often make it impossible to apply the polluter-pays principle, for instance, it has been found that assigning some responsibility to lenders and other deep-pocket parties up or down the value chain might contribute to set incentives right (see Alberini et al 2005, andHiriart andMartimort 2006, among others). Since the benefits of remediation can be unclear, several works have developed rigorous benefit-assessment techniques (see Swartjes 2011, Haninger et al 2014, and the references therein).…”
Section: Introductionmentioning
confidence: 99%